Business Intelligence Requirement Model for Health Care: A Study of Brak Hospital in Libya - Sharafaldeen Mohamed; Belaid Mohammed Addokali; Azizah Ahmad; Ebrahim Ali Elburase (African Journal of Advanced Pure and Applied Sciences, 2022)
The ever-growing nature of organizational data has been requiring the need for business intelligence tools for the purpose of decision support. In recent time, one of the organizations in the lead of experiencing data explosion is health care organizations. Data ranging from the patients’ demographics, medication and diagnosis history, drug repository, medical equipment and others have been posing challenges in health care data management and data-driven decision-making processes, yet all have not been done to attend to this situation. Business Intelligence is yet to be fully employed to attend to data-driven decision-making processes in health care organizations due to insufficient requirement gathering process. This study attends to this observed problem by employing Requirement Management Control (RMC) methodology to present a BI requirement model for health care. Star-schema model was used in the presentation of data dimensions, attributes and facts elicited, negotiated and validated during the RMC phases. Diagnosis history, medication, medical supplier details, patients’ demographics, drug, health insurance providers and medical practitioners’ details are the elicited data needed in health care BI, with the appropriate dimensions and facts duly presented in this study. This serves as a working design document for a full-fledge implementation and development of a functional BI for health care organizations. The limitations and future works are also suggested.